In Vitro Anticancer Activity Guided Investigation Of The Phytochemicals Of Typhonium Flagelliforme (Lodd.) Blume (Araceae) - Lai , Choon Sheen (2010)
Typhonium flagelliforme (Lodd.) Blume is an indigenous plant of Malaysia used as a traditional herbal medicine to treat various types of cancer. In order to effectively understand its pharmacological action, safety and efficacy, it is essential to firstly identify and characterise its chemical constituents and their biological relevance to the healing effect of the plant. A suitable extraction methodology was carefully selected at the preliminary stage of this study. Three types of extraction methods with different modes of action, namely soxhlet, ultrasonic-assisted extraction and maceration methods were evaluated. The maceration method proved to be the most suitable extraction methodology for the purpose of this study with regard to the better activity and greater diversity of the chemical constituents obtained in the extract although the extraction yields were lower. The study also found that extraction carried out using non-polar solvents like hexane and dichloromethane is most suitable in obtaining the active chemical constituents.